Nitrogen fluxes in Urochloa-based pasture soils in the Northwestern Amazon - Villegas, Daniel Mauricio; Arango, Jacobo; Velasquez, Jaime; Krause, Hans Martin; Frossard, Emmanuel; Oberson, Astrid (2024)
Unfertilized grass monocultures with extensive grazing management dominate pastures in Colombia's Caquetá region. These practices contribute to significant nutrient losses, particularly nitrogen (N). Pasture’s N supply could be improved by the inclusion of legumes in pastures (Homem et al. 2021, Thomas, 1992) or grasses with capacity of biological nitrification inhibition (BNI) (Subbarao et al., 2013). Understanding soil N cycling is key to develop strategies that improve sustainability of Amazon pastures’ management.